PEGylated Nanoencapsulate of Melatonin-Rich Supercritical CO2 Extract of Yellow Mustard Seeds is an Authentic Lead for Type 2 Diabetes and Cholesterol Management. Issue 2 (4th March 2022) - Chakraborty, Soumi; Bhattacharjee, Paramita; Chatterjee, Nilendra; Pal, Tapan Kumar
Abstract: This study aimed to formulate melatonin (MT)-rich nanocapsulates from natural sources for mitigating hypercholesterolemia and type 2 diabetes. The in vivo hypocholesterolemic and antidiabetic efficacies of the MT-rich extract of yellow mustard (YM) seeds has already been established in our previous investigation. This outcome prompted us to formulate nanoliposomes of the aforesaid extract to enhance the said therapeutic efficacies. YM extract has been encapsulated in the form of nanoliposomes (YM-PN) and subjected to detailed functional characterization. YM-PN has been administered orally (550 mg/kg b.w. for 28 days) in Wistar albino rats and, post-sacrification their plasma MT level, fasting blood glucose (FBG) level, serum lipid profile and activities of key enzymes of glucose and cholesterol metabolic pathways were assayed. Functional characterization of YM-PN revealed PEGylated-o/w type-hydrophilic nanoliposomes which demonstrated prolonged and sustained release of MT (63.32% after 8 h). A synergistic consortium of antioxidants conferred strong antioxidant activity to YM-PN. Oral administration of YM-PN to diabetic and hypercholesterolemic rats restored their normal FBG and total cholesterol (TC) levels, respectively, with desirable up-down regulations of key enzymes of glucose and cholesterol homeostasis. Plasma MT levels also improved in these animals. The in vitro non-invasive model of iHOMA2 predicted that YM-PN increased hepatic insulin sensitivity and/ or glucose uptake in the gut in diabetic rats. The synergistic consortium of bioactives (including melatonin) in YM-PN is an authentic lead for natural product-based medicines in redressing hypercholesterolemia and type 2 diabetes. Graphical abstract: UF0001